Phalon kay geet - Hussain, Abid (Karachi : Paramount books, 2009)
This Urdu book, "Phalon Kay Geet," translates to "Songs of Fruits." It likely contains simple poems or stories about different tasty fruits.
Location: 2B
Keywords: Rhymes